2005
DOI: 10.2337/diacare.28.12.2832
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Glycemic Index and Glycemic Load, Carbohydrate and Fiber Intake, and Measures of Insulin Sensitivity, Secretion, and Adiposity in the Insulin Resistance Atherosclerosis Study

Abstract: OBJECTIVE -We studied the association of digestible carbohydrates, fiber intake, glycemic index, and glycemic load with insulin sensitivity (S I ), fasting insulin, acute insulin response (AIR), disposition index, BMI, and waist circumference.RESEARCH DESIGN AND METHODS -Data on 979 adults with normal (67%) and impaired (33%) glucose tolerance from the Insulin Resistance Atherosclerosis Study (1992)(1993)(1994) were analyzed. Usual dietary intake was assessed via a 114-item interviewer-administered food freque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
160
1
5

Year Published

2006
2006
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 233 publications
(180 citation statements)
references
References 49 publications
14
160
1
5
Order By: Relevance
“…Fiber, glycemic index and load, and obesity K Murakami et al in previous cross-sectional studies (Appleby et al, 1998;Sasaki et al, 2003;Spencer et al, 2003;Howarth et al, 2005;Liese et al, 2005), although one study did not show an inverse association (Stookey, 2001). Higher total dietary fiber intake has also been associated with lower body weight gain (Ludwig et al, 1999) and lower increase in body weight and BMI (Liu et al, 2003) in several prospective studies.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…Fiber, glycemic index and load, and obesity K Murakami et al in previous cross-sectional studies (Appleby et al, 1998;Sasaki et al, 2003;Spencer et al, 2003;Howarth et al, 2005;Liese et al, 2005), although one study did not show an inverse association (Stookey, 2001). Higher total dietary fiber intake has also been associated with lower body weight gain (Ludwig et al, 1999) and lower increase in body weight and BMI (Liu et al, 2003) in several prospective studies.…”
Section: Discussionmentioning
confidence: 94%
“…Several ad libitum trials conducted on nondiabetic subjects have suggested a beneficial effect of low-GI diet on fat mass (Bouche et al, 2002) and body weight (Bouche et al, 2002;Sloth et al, 2004), when compared with high-GI diet, although other trials conducted on subjects with type II diabetes have found no differences in body weight change between high-and low-GI diets (Heilbronn et al, 2002;Jimenez-Cruz et al, 2003;Rizkalla et al, 2004). Additionally, although there has been no association between dietary GI and GL and BMI in some studies (Amano et al, 2004;Liese et al, 2005), other observational studies have shown a positive association between dietary GI, but not dietary GL and BMI Murakami et al, 2006b).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although many researchers have applied GI estimation values to dietary assessment instruments [14][15][16][17], the methodology used to obtain these values has only recently been documented in detail in a few studies using the food frequency questionnaire (FFQ) [17][18][19]. However, although similar, description of methodology in assigning GI values in 24-hour dietary recalls (24HRs) is currently lacking.…”
Section: Introductionmentioning
confidence: 99%